(untitled) (The East and Central African Journal of Pharmaceutical Sciences, 2020)
It is reasonable to conclude that a common source of pharmacotherapeutic failure is misdiagnosis and much more so in case of self-medication. Other factors that contribute to the therapeutic failure can be grouped into two broad categories, namely drug-related and patient-related factors. Let us focus on the drug-related factors. Firstly, the dosage may be inadequate, due to ingestion of drug products of poor quality. In this issue of the journal, there are two articles on the quality of sulphadoxine/ pyrimethamine (SP) products currently being used in Kenya and Tanzania.